1966
DOI: 10.2466/pms.1966.23.3f.1311
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Shock Intensity, Age, and Handling Effects on Avoidance Conditioning

Abstract: 180 rats aged 3 or 300 days were either handled for 20 consecutive days or were unhandled. 40 days after treatment, rats learned a discriminated avoidance task, with 1 of 3 UCS (shock) intensities. Handling improved avoidance performance of both 3- and 300-day-old Ss with mild (0.5-ma.) and moderate (1.0-ma.) shock intensities. Avoidance performance of infantile-handled rats was superior to performance of other Ss at lower shock levels but was inferior to other groups with a stronger shock level (2.0 ma.). Per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1969
1969
1986
1986

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Since numerous studies showed that males and females are affected differentially by early handling (Erskine, Stem, & Levine, 1975;Hughes, 1968;Weinberg, Krahn, & Levine, 1978;Wells, 1976;Wong & Judd, 1973), we tested the effects of early handling on the development of LI in male and female rats. The procedure used to assess LI was two-way active avoidance, which has been shown to be sensitive to early handling (e.g., Denenberg & Smith, 1963;Doty & O'Hare, 1966). Animals were pre-exposed to a series of tones that served later as the CS in avoidance.…”
mentioning
confidence: 99%
“…Since numerous studies showed that males and females are affected differentially by early handling (Erskine, Stem, & Levine, 1975;Hughes, 1968;Weinberg, Krahn, & Levine, 1978;Wells, 1976;Wong & Judd, 1973), we tested the effects of early handling on the development of LI in male and female rats. The procedure used to assess LI was two-way active avoidance, which has been shown to be sensitive to early handling (e.g., Denenberg & Smith, 1963;Doty & O'Hare, 1966). Animals were pre-exposed to a series of tones that served later as the CS in avoidance.…”
mentioning
confidence: 99%
“…Campbell (1967) was unable to find age-related differences in the aversive threshold to grid shock in the rat, but the age range studied by Campbell was relatively narrow since only 25-, 50-, and 100-day-old rats participated in his study. On the other hand, the work of Doty and O'Hare (1966) suggests that the aversive threshold is higher in 360-day-old rats compared with 63-dayold rats, and that the age differences observed in avoidance performance are abolished with increases in the US shock. Weiss (1959) reports that with the dog, sensitivity to nociceptive stimulation decreases with age.…”
Section: Discussionmentioning
confidence: 99%
“…Another variable of concern was the intensity of the "US shock used in the CER procedure. Doty and O'Hare (1966) have presented data suggesting that grid shock may have different motivational properties for animals of different ages. For this reason the present investigation attempted to evaluate the relative effect of different shock intensities on the acquisition of a CER by young and old rats.…”
mentioning
confidence: 99%
“…Donovick et al (I973) included periodic handling of animals in their presurgical environmental/social enrichment conditions. It is well documented that handling per se, either during early developmental stages (e.g., Denenberg, 1964;Levine, 1962;Williams, Bailey, & Lee, 1975) or later in life (e.g., Doty, 1968;Doty & O'Hare, 1966), can be an important determinant of subsequent behavior displayed by intact as well as septal-damaged animals. Indeed, both pre-and postsurgical handling may reduce the relatively transient "hyperemotionality" component of the so-called septal syndrome (cf.…”
Section: Presurgical Handling and Exploratory Behaviormentioning
confidence: 99%